2011
DOI: 10.1152/ajpheart.01164.2010
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Na/K pump activity by chronic intermittent hypobaric hypoxia protected against reperfusion injury

Abstract: Chronic intermittent hypobaric hypoxia (CIHH) has been shown to attenuate intracellular Na+ accumulation and Ca2+ overload during ischemia and reperfusion (I/R), both of which are closely related to the outcome of myocardial damage. Na/K pump plays an essential role in maintaining the equilibrium of intracellular Na+ and Ca2+ during I/R. It has been shown that enhancement of Na/K pump activity by ischemic preconditioning may be involved in the cardiac protection. Therefore, we tested whether Na/K pump was invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 46 publications
(42 reference statements)
0
17
0
Order By: Relevance
“…The integrity of some subcellular structures, particularly the mitochondrial membrane and interior cristae, of cardiomyocytes in animals with massive blood loss were well preserved, as verified by the changes of MMP27, cyt c 2829 and Na-K-ATPase30. In the myocardium, oxidative phosphorylation in the mitochondria is the primary means of ATP synthesis.…”
Section: Discussionmentioning
confidence: 86%
“…The integrity of some subcellular structures, particularly the mitochondrial membrane and interior cristae, of cardiomyocytes in animals with massive blood loss were well preserved, as verified by the changes of MMP27, cyt c 2829 and Na-K-ATPase30. In the myocardium, oxidative phosphorylation in the mitochondria is the primary means of ATP synthesis.…”
Section: Discussionmentioning
confidence: 86%
“…Meanwhile, Zheng et al [25] found that the protection from cardiac injury may be determined by the Na + -K + -ATPase activity, involving ERK1/2 and PI3 K/Akt signal pathways. Furthermore, continued intermittent hypobaric hypoxia can reduce the reperfusion injury in guinea pig by increasing myocardial Na + -K + -ATPase activity [26]. The Na + -K + -ATPase consists of α and β subunits; the α subunit is responsible for the catalytic activity of the enzyme and includes three isoforms: α 1 , α 2 , and α 3 in the rat heart.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that CIH can induce preconditioning-like effect to effectively protect the heart against ischemia/reperfusion (I/R) or hypoxia/reoxygenation-induced injury [16, 8–11, 64, 65], including the prevention of I/R-induced cardiac apoptosis and necrosis [3, 5] arrhythmias [6]. CIH also can improve postischemic recovery of cardiac function [1].…”
Section: Cardiac Response To Cih: a Transition From Adaptation To mentioning
confidence: 99%